Sustainable E-learning and Education with Intelligence - Lin, Hao-Chiang Koong (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this era of rapid technological evolution, the landscape of education continually transforms. This compilation is a timely endeavor, capturing the intersection of technology and learning, a synergy pivotal for the future. This anthology, a mosaic of innovation and insight, beckons readers to witness the dawn of a transformative epoch in education.